2020
DOI: 10.3390/ijerph17165643
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Stretching Exercises on Arterial Stiffness in Middle-Aged and Older Adults: A Meta-Analysis of Randomized and Non-Randomized Controlled Trials

Abstract: Background: Aerobic exercise is known to reduce arterial stiffness; however, high-intensity resistance exercise is associated with increased arterial stiffness. Stretching exercises are another exercise modality, and their effect on arterial stiffness remains unclear. The purpose of this study was to determine whether stretching exercises reduce arterial stiffness in middle-aged and older adults, performing the first meta-analysis of currently available studies. Methods: We searched the literature for randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Waist circumference decreased more in the walking (108 [13] to 103 [10] cm) compared with the stretching (100 [15] to 100 [16] cm) group (group × time; P = .029). There was no change in body mass over time for either group (data not shown).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Waist circumference decreased more in the walking (108 [13] to 103 [10] cm) compared with the stretching (100 [15] to 100 [16] cm) group (group × time; P = .029). There was no change in body mass over time for either group (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…Our purpose was to compare walking and stretching exercise programs in people with moderately elevated blood pressure. A recent meta-analysis of stretching programs 13 indicates similar reduction in systolic blood pressure (ie, −3.9 mm Hg) but potentially higher reduction in diastolic blood pressure (ie, −2.7 mm Hg) compared with recent meta-analyses of walking programs (reduction in systolic blood pressure of −3.1 to −4.1 mm Hg and reduction in diastolic blood pressure of −1.5 to −1.8 mm Hg). [14][15][16] The only study to compare a stretching to a walking program (in sedentary pregnant women) found that stretching was superior for reducing blood pressure (systolic blood pressure of −4 mm Hg and diastolic blood pressure of −1 mm Hg) compared with walking (systolic blood pressure of +5 mm Hg and diastolic blood pressure of +4 mm Hg).…”
mentioning
confidence: 99%
“…A growing body of evidence regarding the effects of stretching and vascular health is present. Two recent meta-analyses have investigated the effects of stretching on arterial stiffness [ 110 , 111 ]. The results of both investigations are based on a partial overlap of the included records; therefore, these present similar outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies report a decrease in arterial stiffness as a consequence of stretching. The study of Kato et al [ 111 ] only included longitudinal interventions, while the study of Thomas et al [ 110 ] also included acute forms of exercise. The authors of this last investigation state that the moderator analysis regarding the length of the intervention did not highlight significant differences, which underpins that acute stretching bouts may also be able to decrease arterial stiffness, both central (carotid–femoral PWV) and systemic (brachial–ankle PWV).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should find out to what extent RT parameters, stretching and aerobics affected AS. Recent meta-analyses demonstrated that stretching reduced AS, HR, and DBP and improved endothelial function, all of which are crucial parameters of arteriosclerosis in middle-aged and older adults [96]. Another important thing that cannot be neglected is the location of PWV measurement.…”
Section: Discussionmentioning
confidence: 99%